Analisis Keefektifan Metode Game Edukatif terhadap Keaktifan dan Kerja Sama Siswa Sekolah Dasar - Afriani, Widya; Nisa, Sahrun (Lembaga Yasin AlSys, 2024)
The application of learning methods is still lacking so most students may feel bored and unmotivated during lessons because learning methods have not been applied properly. In addition, the limited use of media in the learning process causes students' lack of understanding of what they are learning and students' activeness is not seen during the learning process. The purpose of this article is to determine the effectiveness of educational games. Many people use media as an additional tool for learning due to technological advances that occur in the current era of globalization. The use of media in learning aims to make the educational game method effective in increasing student engagement and cooperation in elementary schools. In addition, the use of media makes it easier for teachers to convey material and make students better understand what they are learning. Therefore, teachers must ensure that the materials and media used are appropriate. This article will discuss the use of game-laden interactive multimedia in learning in elementary school. It will also analyze the participation and cooperation of students in primary schools as well as the factors that influence the application of game-laden interactive methods in the learning process.